Is in situ simulation in emergency medicine safe? A scoping review - Guillaume Martel; Andrew Petrosoniak; Marcel Émond; Jennifer Truchot; Valérie Boucher; Éliane Raymond-Dufresne; Winny Li; Eva Jouhair (BMJ Open)
Objectives To provide an overview of the available evidence regarding the safety of in situ simulation (ISS) in the emergency department (ED).Design Scoping review.Methods Original articles published before March 2021 were included if they investigated the use of ISS in the field of emergency medicine.Information sources MEDLINE, EMBASE, Cochrane and Web of Science.Results A total of 4077 records were identified by our search strategy and 2476 abstracts were screened. One hundred and thirty full articles were reviewed and 81 full articles were included. Only 33 studies (40%) assessed safety-related issues, among which 11 chose a safety-related primary outcome. Latent safety threats (LSTs) assessment was conducted in 24 studies (30%) and the cancellation rate was described in 9 studies (11%). The possible negative impact of ISS on real ED patients was assessed in two studies (2.5%), through a questionnaire and not through patient outcomes.Conclusion Most studies use ISS for systems-based or education-based applications. Patient safety during ISS is often evaluated in the context of identifying or mitigating LSTs and rarely on the potential impact and risks to patients simultaneously receiving care in the ED. Our scoping review identified knowledge gaps related to the safe conduct of ISS in the ED, which may warrant further investigation.